(3TQM OjhGf GdCQjH aj eNJUQ eYfi GddHjHs - (3eMeO Hf YHO GdeLjO GdSGehdj GdSYhOj GdTGaYj,J (B961 (3g` s ((3ESeGYjd Hf eMeO Hf CHj GdaJM GdOfhTQj GdTGaYj s)
(3ChdgG (B:s
(3hHYO, abO Cdgefj Gddg JYGdi hTQM UOQj Cf CfJNH dj ef eYfi GddHjH ddYdGeI GHf gTGe s
(3BNQgG (B:s
(3hef cJH GHf eGdc, hcGajI GHf GdMGLH, hQHeG GdJbW ef ZjQ Pdc eUQMkG Hg ZGdHkG hZjQ eUQM hGdMeO ddg s
(3ajg VHW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3eZfj GddHjH dGHf gTGe GdCfUGQj GdeJhai Sf``(B761(3``Is
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs